Code mixing analysis on Daniel Mananta’s youtube channel video: Sociolinguistic Approach - Afriani Rismauli Simanungkalit; Emil Eka Putra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
This research examines the code mixing in YouTube video content. Researchers use youtube video Daniel Mananta’s because every video content he always uses a code-mixing which is his trademark and sees from background of his life. For this situation, researchers apply code-mixing on Daniel Mananta's youtube content. The this research is to determine the type of code mixing and the code mixing factors contained in Daniel Mananta's youtube conten.analysis to be conducted to Hoffman (1991).   Researchers used qualitative descriptive method techniques according to Sudaryanto (2015).  The technique of collecting data by observation and listening to conversations in the content then records the mixed code contained in the content. From this study, researchers found 23 types of intra-sentential information, 6 intra-lexical data, and 1 type including changes in articulation or speech. Researchers found that there are factors that influence code mixing such as discussing certain points, exciting.keywords: sociolinguistics, code mixing.